Patterns of emigration among Ural Germans in 1929–1930 (based on local research) - Avdashkin A.A. (Вестник археологии, антропологии и этнографии, 2019)
In the 20th and early 21st century, the South Ural region, which is located at the crossroads of Asia and Europe, was the focus of routes of cross-border migration. This migration was both voluntary and forced. Ethnic German peoples have played a prominent role in the ethnic history of the region over the past three centuries. Russian Germans are a clear example of a «people on the move» (in German «Volk auf dem Weg»). The history of this ethnic group is inextricably linked with migration and adaptation to the conditions in the host society. In this case, we can talk about a kind of migratory ebb and flow, when in certain historical periods the emigration of Germans from Russia increased. One of these pages in the history of Russian Germans is the period of collectivization. In this article, the story about the emigration attitudes of German colonists in the Troitskiy district of the Ural Region in the winter of 1929–1930 is reviewed. Material for the article is provided by documents of the state archive of the Chelyabinsk region. This case-study fits well into the general context of the history of Russian Germans during the period of collectivisation and substantively complements the history of the Germans of the Urals. The transformations that were carried out in the villages led to an increase in desire to emigrate among the German population. The author describes the situation that developed in the German colonies of the Troitskiy district. German colonists retained their traditional ways of life and mindsets, so they did not have the opportunity to take part in socialist reconstruction of the countryside. German peasants were perceived by the authorities as holding on to alien ideologies and being a favourable environment for hostile propaganda. The forced modernisation of the Stalinist period (especially collectivisation and the «cultural revolution») became a powerful factor that transformed the entire way of life of Russian Germans and their ethno-cultural identity.